Homeland : my father dreams of Palestine - Moushabeck, Hannah (Chronicle Books LLC, 2023)
"A Palestinian family celebrates the stories of their homeland in this moving autobiographical picture book debut by Hannah Moushabeck. With heartfelt illustrations by Reem Madooh, Homeland: My Father Dreams of Palestine is a love letter to home, to family, and to the persisting hope of people, which transcends borders"--